Development of a Measure for Assessing Perceived Community Culture Based on Triandis's Horizontal/Vertical Individualism-Collectivism Cultural Orientation - Albina Alikovna Gallyamova; Dmitry Sergeevich Grigoryev (Peoples' Friendship University of Russia (RUDN University), 2022)
A new measure based on Triandis's horizontal/vertical individualism-collectivism cultural orientation was developed to assess perceived community culture though the lens of horizontal individualism, vertical individualism, horizontal collectivism, and vertical collectivism. In the first step, a qualitative analysis using cognitive interviews showed that item wordings were appropriate to the Russian context, meaningfully accurate, and tangible to participants. In the second step, there was empirical testing of measure with 300 participants of the sociopsychological survey (questionnaire). The results showed that the expected factor structure had acceptable global and local fit of measurement model with the collected data. The measures had measurement equivalence by gender and acceptable indicators of reliability and validity. Comparison of obtained results with those published earlier showed that presented measure of the cultural orientations provided better model fit and indicators than the original measure or its other modifications, adaptations, and translations into Russian. Moreover, the developed measure showed that the assessment results were meaningfully correlated with the individual values of the participants assessed by Schwartz's basic human values approach. Finally, the measure is particularly useful and can be successfully applied in a variety of studies aimed to study social influence. The questionnaire in English is available at Appendix in the end of the paper.